A Critical Assessment of Evidence-Based Policy and Practice in Social Work. Issue 4 (3rd July 2016) - Diaz, Clive; Drewery, Sian
Abstract : In this article the authors consider how effective social work has been in terms of evidence-based policies and practice. They consider the role that "evidence" plays in policy making both in the wider context and, in particular, in relation to social work. The authors argue that there are numerous voices in the policy-making process and evidence only plays a minor role in terms of policy development and practice in social work.